Aplikasi Sistem Informasi Geografis dan Penginderaan Jauh untuk Kajian Potensi dan Kerawanan Longsor di Daerah Aliran Sungai Tukad Buleleng, Kabupaten Buleleng - WINDA ARDY DWIASTUTI; WIYANTI WIYANTI; I WAYAN DIARA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2021)
Application of Geographic Information Systems and Remote Sensing for The Study of Landslide Potential and Susceptibility in Tukad Buleleng Watershed, Buleleng Regency Landslides are a ground movement event that descends the slopes and is almost found in every major watershed upstream, due to steep topography and high rainfall. Tukad Buleleng watershed is one of the watersheds with a stretch of rolling land and hills so that it has the potential for landslides. This experiment was been conducted from January to Agust 2020. The aims off this research were to find out the potential lanslide and the level susceptibility to landslide. The method used to determine the potential for landslides was a scoring method referring to PSBA UGM (2001) by overlapping the parameters of the causes of landslides were rainfall, slope, land use, soil types, structural of geology, and landforms maps. Landslide-prone areas were obtained by overlapping landslide potential map, road network map and residential area map. The results showed that the potential landslide in Tukad Buleleng watershed had many categories from not potentially up to high potential. The area had no potential of landslide were widespread in the downstream watershed covering an area of 1,733.94 ha 51.61%, low potential category of 165.08 ha 4,91%, the medium potential category of 77.24 ha 2,32%, and high potential category spread over the upstream part of the watershed of 1,382.87 ha 41,16%. The distribution of susceptibility was seen from administrative boundaries, Sukasada administration area that covered Wanagiri, Pegayaman, Gitgit, and Padangbulia villages.